Personality in History and History of a Personality: A View from Russia on the Role of Getúlio Vargas in the Fate of Brazil - D. A. Kuznetsov (Ибероамериканские тетради)
Book Review: Martynov B.F. Getulio: a novel-biography. – Moscow: MGIMO University, 2022 (in Russian). – 458 p.